Transforming EFL Instruction: A Systematic Review of Chatbot Integration in English Language Learning - Made Natya Pradnya Iswari; Santosa, Made Hery; Indrayani, Luh (Universitas Pendidikan Ganesha, 2024)
There are important areas that have not been fully investigated. The use of chatbots to improve students' language learning abilities presents various advantages and obstacles. This study explores the integration of Chatbots in English language instruction for EFL learners, focusing on their impact on learning implementation experiences, advantages, and limitations. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards, the research reviewed articles from 2019 to 2024 to ensure a comprehensive analysis. A total of 998 publications were identified through Google Scholar, with search terms such as